Draft Ninth Five Year Plan 1997-2002 and Annual Plan 1997-98 Volume II Government of Uttar Pradesh - Planning Commission (Planning Commission, 1997)
Major Headwise Proposed Outlay, Sub-Plan and Annual Plan (1997-98) and Special Hill Assistance, Uttaranchal Draft Ninth Plan (1997-2002), Sub-Plan and Annual Plan (1997-98), Physical Targets and Achievements, Uttaranchal Draft Ninth Plan (1997-2002) Externally, Sub-Plan and Annual Plan (1997-98) Aided Project, Externally Aided Project Physical Targets and Achievement.
Government of Uttar Pradesh Uttaranchal Vikas Vibhag